Cultures and Identities in Transition : Jungian Perspectives. - Stein, Murray (Taylor & Francis, 2010)
Offering a thematic approach which looks at personal and cultural identities in relation to Jung's own identity and the identities of contemporary Jungians, this book returns to the roots of analytical psychology.